Location Selection Criteria for the Sea Passenger Terminal in Relation to the Urban Structure of the Town - Deluka-Tibiljaš, Aleksandra; Lučić, Sanja; Benigar, Milivoj (Promet - Traffic&Transportation, 2006)
A typical Mediterranean town develops as a rule around itshistorical nucleus which may be longitudinally set parallel tothe coastline or concentrated in the area of a minor or majorpeninsula or located in a bay. These towns are usually characterizedby heavy build-up in the area of a wider town centre, insufficienttraffic network and insufficient number of parkingspaces, and finally a conflict between the urban structure andthe terminals which aspire at tending to occupy the same space.The work analyzes the potential criteria that need to be respectedin selecting the location of the sea terminal regarding itsfunctioning in relation to the town and urban traffic. The comparisonof certain indicators related to the maritime passengertraffic of eight bigger European ports of the Mediterranean, aswell as in four major Croatian sea passenger ports, has beenmade. The objective of the work is to define the possible criteriaof assessing the location of the passenger sea terminal and todevelop the assessment method for each of the criteria.